Economic Growth in ASEAN-4 Countries: A Panel Data Analysis - Nooraini, Saidin (2012)
This research studies the impact of economic variables which are foreign direct investment (FDI), openness and gross fixed capital formation to economic growth which indicates using gross domestic product (GDP). Data is collected from 1981 until 2008 using World Development Indicator CD-ROM. This research estimates using panel data estimation. In order to test the significance of the variable, this research uses panel unit root test. Result of panel data unit root test shows that all variables in panel unit root test are significant and stationary at first difference 5 percent level of significant. In addition, the impact of variables to GDP is estimated using three panel estimation models which are called pooled model (pooled), fixed effects model (FEM) and random effects model (REM). Result of three particular models in panel estimation give the stationary at 5 percent level of significant for all variables involved. Variable of openness for pooled and random effects model indicate negative relation with GDP. Meanwhile, other variables in all models show positive relation with GDP. Goodness to fit in this research for all models demonstrate high value which 0.74 (pooled), 0.87 (FEM) and 0.73 (REM). Furthermore, Hausman test is employed to this research in order to choose the best model. Result for this test suggests rejecting null hypothesis because of the value of p is 0.00 (p<.05). On other words, rejecting of null hypothesis may conclude that the FEM will apply. Thus, this research describes that all variables are correlated with each other and also have the positive relationship to GDP. Hence, all variables may lead economic growth boost when they are increase whereas FDI becomes the most efficient variable in order to assist economic growth and followed by openness and gross fixed capital formation. Otherwise, the result in Ordinary Least Squares (OLS) which implies in this study as well test all variables stationary at 5 percent level of significant. These shows only gross fixed capital formation is significant to growth and contributes the positive effect to GDP in each ASEAN-4 countries. However, OLS estimation result for Indonesia shows the other variable has significant to growth which is openness; while it gives the negative affect the GDP. Instead of Indonesia, openness is not significant at other ASEAN-4 countries such as Malaysia, Thailand and Philippines. Besides, other variable is FDI also not significant in the case of all ASEAN-4 countries. It means that, openness does not correlated to growth for Malaysia, Thailand and Philippines countries; while FDI is not correlated to growth for all ASEAN-4 countries in this study.